Resveratrol has an Overall Neuroprotective Role in Ischemic Stroke: A Meta-Analysis in Rodents - Liu, Jianyang; He, Jialin; Huang, Yan; Hu, Zhiping (Frontiers in Pharmacology, 2021)
Background: Resveratrol, a natural polyphenolic phytoalexin, is broadly presented in dietary sources. Previous research has suggested its potential neuroprotective effects on ischemic stroke animal models. However, these results have been disputable. Here, we conducted a meta-analysis to comprehensively evaluate the effect of resveratrol treatment in ischemic stroke rodent models. Objective: To comprehensively evaluate the effect of resveratrol treatment in ischemic stroke rodent models. Methods: A literature search of the databases Pubmed, Embase, and Web of science identified 564 studies that were subjected to pre-defined inclusion criteria. 54 studies were included and analyzed using a random-effects model to calculate the standardized mean difference (SMD) with corresponding confidence interval (CI). Results: As compared with controls, resveratrol significantly decreased infarct volume (SMD −4.34; 95% CI −4.98 to −3.69; p < 0.001) and the neurobehavioral score (SMD −2.26; 95% CI −2.86 to −1.67; p < 0.001) in rodents with ischemic stroke. Quality assessment was performed using a 10-item checklist. Studies quality scores ranged from 3 to 8, with a mean value of 5.94. In the stratified analysis, a significant decrease of infarct volume and neurobehavioral score was achieved in resveratrol sub-groups with a dosage of 20-50 mg/kg. In the meta-regression analysis, the impact of delivery route on an outcome is the possible source of high heterogeneity. Conclusion: Generally, resveratrol treatment presented neuroprotective effects in ischemic stroke models. Furthermore, this study can direct future preclinical and clinical trials, with important implications for human health.